2009
DOI: 10.1105/tpc.108.061663
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Nuclear Bodies of Arabidopsis CRY2 in Response to Blue Light Is Associated with Its Blue Light–Dependent Degradation

Abstract: Arabidopsis thaliana cryptochrome 2 (CRY2) mediates photoperiodic promotion of floral initiation and blue light inhibition of hypocotyl elongation. It has been hypothesized that photoexcitation derepresses CRY2 by disengaging its C-terminal domain from the N-terminal PHR domain. To test this hypothesis, we analyzed activities of CRY2 fused to green fluorescent protein (GFP) at either the N terminus (GFP-CRY2) or the C terminus (CRY2-GFP). While GFP-CRY2 exerts light-dependent biochemical and physiological acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
167
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(178 citation statements)
references
References 42 publications
10
167
0
1
Order By: Relevance
“…a cop-like phenotype in dark-grown seedlings (28,29). Interestingly, when 3-day-old CCT2 or 4-day-old CRY2-GFP etiolated seedlings were transferred to white light, we found that most of their cotyledons were unable to turn green ( Fig.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…a cop-like phenotype in dark-grown seedlings (28,29). Interestingly, when 3-day-old CCT2 or 4-day-old CRY2-GFP etiolated seedlings were transferred to white light, we found that most of their cotyledons were unable to turn green ( Fig.…”
mentioning
confidence: 90%
“…S1]. Conversely, a GFP-CRY2 overexpressing line that failed to show a cop-like phenotype (29) exhibited a normal cotyledon greening process (Fig. 1B and Fig.…”
mentioning
confidence: 99%
“…1 There are 2 highly similar cryptochrome genes in Arabidopsis with overlapping functions but somewhat different light sensitivity; cry1 is stable at high light intensity whereas cry2 is rapidly degraded in the presence of blue light due to ubiquitination and targeting to the proteasome. 2 Until the present time, attempts to understand the mechanism of cry activation have focused on light-driven conformational change in the receptor that lead to interaction with transcription factors and/or elements of the proteasome. Certain changes in gene expression, for instance in the induction of flowering time and in de-etiolation responses have indeed been convincingly linked to cryptochrome interaction with these biological partners (reviewed in 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fitting equation (18) to the experimentally measured number distribution we obtained an estimate for N s . Fitting equation (15) to the experimentally measured volume distribution we obtained estimates for δ, Δ, γ and the product K N s using ν = 0.64 and V 0 = 2.7× 10 −7 μm 3 . Using the estimate for N s we then obtained an estimate for K. For the maximum likelihood we used the fitdistr of the MASS package implemented in R [33].…”
Section: Estimating Association and Dissociation Parameters From Expementioning
confidence: 99%
“…Photoreceptors change conformation upon being activated by specific wavelengths of light and are subsequently transported to the nucleus where they form NBs, also sometimes referred to as spots or speckles. Notably, cryptochrome 2 (cry2) and two members of the phytochrome family, the light-labile phytochrome A (phyA) and light-stable phytochrome B (phyB), have been shown to form NBs when exposed to the required activating light conditions [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%